2020
DOI: 10.1038/s41598-019-56760-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical stimuli on hair follicle deposition of clobetasol-loaded Lipid Nanocarriers

Abstract: Clobetasol propionate (CLO) is a potent glucocorticoid used to treat inflammation-based skin, scalp, and hair disorders. In such conditions, hair follicles (HF) are not only the target site but can also act as drug reservoirs when certain formulations are topically applied. Recently, we have demonstrated nanostructured lipid carriers (NLC) containing CLO presenting epidermal-targeting potential. Here, the focus was evaluating the HF uptake provided by such nanoparticles in comparison to a commercial cream and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Additionally, a manual massage increased more than twice the amount of clobetasol accumulated into the hair follicles. 56 Indeed, the motion induced the nanosystem's deposition inside the hair follicles with maximal velocity, which stimulates the entrapped drug deposition in these structures, as revealed before. 77 Deformable nanoparticles have also been studied to topically deliver other drugs with undesirable systemic side effects, such as flutamide.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Additionally, a manual massage increased more than twice the amount of clobetasol accumulated into the hair follicles. 56 Indeed, the motion induced the nanosystem's deposition inside the hair follicles with maximal velocity, which stimulates the entrapped drug deposition in these structures, as revealed before. 77 Deformable nanoparticles have also been studied to topically deliver other drugs with undesirable systemic side effects, such as flutamide.…”
mentioning
confidence: 60%
“… [ 47 ] Clobetasol propionate Nanostructured lipid carriers 180 Skin from porcine ears Nanoparticles released the drug in a sustained fashion for more than 3 days and increased passively in about 40 times the clobetasol follicular uptake, compared to the commercial cream. [ 56 ] Diphencyprone Nanostructured lipid carriers 208–265 Nude and hairy mouse dorsal skin A more regular absorption of diphencyprone was achieved by applying nanostructured lipid carriers compared to the control. [ 57 ] Diphencyprone and Minoxidil Nanostructured lipid carriers and nanoemulsions 177 and 194 Female nude mice (ICR-Foxn1nu) Follicular uptake by squarticles was 2- and 7-fold higher for diphencyprone and minoxidil, respectively, compared to the free drug controls.…”
Section: Challenges Of Current Topical Treatments For Alopeciamentioning
confidence: 99%
“…Lipid nanoparticles have been used as an alternative TDDS for pharmaceutical drugs and cosmetic compounds since the early 1990s [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. A solid lipid nanoparticle (SLN) was prepared by the exchange of the liquid lipid oil of the emulsions by solid lipid, which remains at a solid-state at room temperature and body temperature [ 66 , 67 ].…”
Section: Transdermal Drug Delivery Using Nanocarriermentioning
confidence: 99%
“…For the improvement of these lipid-based nanocarriers, Park et al developed lipid nanoparticles composed of ceramide and succeeded in TDDS of apigenin [ 76 ]. Gratieri et al reported clobetasol-loaded lipid nanocarriers and investigated the effects on hair follicles [ 77 ]. In addition, Hamada et al successfully prepared ultra-small nanoparticles by using anionic phospholipids.…”
Section: Transdermal Drug Delivery Using Nanocarriermentioning
confidence: 99%
See 1 more Smart Citation